CLINICAL EVIDENCE OF THE MULTIFACTORIAL NATURE OF DIABETIC MACULAR EDEMA. Issue 2 (February 2018) - Chakravarthy, Usha; Yang, Yit; Lotery, Andrew; Ghanchi, Faruque; Bailey, Clare; Holz, Frank G.; Downey, Louise; Weber, Michel; Eter, Nicole; Dugel, Pravin U.
Abstract : Purpose: To report functional and morphologic outcomes, based on diabetic macular edema (DME) chronicity and baseline best-corrected visual acuity (BCVA), from a subanalysis of the fluocinolone acetonide for macular edema (FAME) trials. Methods: Patients were categorized by DME duration (nonchronic [ncDME] or chronic [cDME] DME) and three nonexclusive baseline vision strata. Anatomic and visual acuity VA outcomes of these cohorts were compared with treatment assignment. Results: For all patients with ncDME and cDME who received sham control, 27.8% and 13.4%, respectively, gained ≥15 BCVA letters, whereas 22.3% and 34.0% of 0.2 μ g/day fluocinolone acetonide (FAc)-treated patients, respectively, gained ≥15 BCVA letters. Among patients with ncDME who received sham control, as baseline vision decreased, the percentage gaining ≥15 BCVA letters increased; however, among those with cDME, the percentage gaining ≥15 BCVA letters did not change as baseline vision decreased. Conversely, among 0.2 μ g/day FAc-treated patients, the percentage gaining ≥15 BCVA letters increased with decreasing baseline vision, regardless of DME chronicity. Anatomical outcomes were similar within treatment arms, regardless of the DME duration. Conclusion: Patients with cDME and poor baseline vision who were exposed to low-dose FAc experienced BCVA improvements that were not observed in a similar group from the sham-control arm. These data support the multifactorial pathogenesis of cDME. Abstract : As the disease duration increases, the multifactorial nature of diabetic macular edema becomes more prominent, and corticosteroid therapy represents an important treatment option for patients whose disease is multifactorial.